Literacy Dice Puzzle Learning Media to Improve Literacy Skills of Grade V Elementary School Students - Mila Indriati; Bagus Amirul Mukmin; Kukuh Andri Aka; Rian Damariswara (Universitas Pendidikan Ganesha, 2025)
The lack of reading culture at home and in the surrounding environment impacts low student literacy. Based on this, this study aims to develop a game-based learning media,